Essays on foreign direct investment: some missing pieces - Fernandez-Delgado, K (2018)
This thesis contains three chapters. All are based on firm-level data for Chile between the mid-1990s and the mid-2000s, and all concern the effects of foreign direct investment: the first and second chapters are about the gender balance of employment and training, respectively, while the third analyses how productivity spillovers depend on distance from the productivity frontier.